PERBANDINGAN CITRA MRI PEDIS SEQUENCE PROTON DENSITY FAT SATURATED DAN STIR (SHORT TAU INVERSION RECOVERY) POTONGAN SAGITAL - Wahyudiarti, Endah; Winarno, Guntur; Gunawati, Shinta; Prananto, Legia; Heru, Nursama (JRI (Jurnal Radiografer Indonesia), 2021)
Bakcground: The differences in fat suppression MR images between Proton Density Fat Saturated sequence with STIR sequence in MRI pedis sagital view. This research aims to analyze the differences of SNR, CNR, and the details MR images. Methods: Secondary data were using by non-probability sampling technique with 10 purposive sampling of pedis MR images Proton Density Fat Saturated sequence and STIR sequence sagittal view in DICOM were done by using imageJ software. The instrument of this research consisted of a worksheet and questionnaire. Result: This research showed SNR p value/sig 0,000 < 0,05 and CNR p value/sig 0,575 > 0,05. In Proton Density Fat Saturated sequence sagittal view the detail of ekstra-articular fluids value is 1,76, tendon Achilles value is 2,88, joint space value is 2,86 and bone marrow value is 2,04, contrast resolution value is 2,418, noise ratio value is 2,32. Pedis MR images of STIR sequence sagittal view the details of ekstra-articular fluids value is 2,92, tendon Achilles value is 3,28, joint space value is 2,84 and bone marrow value is 3,4, contrast resolution value is 3,022 and noise ratio value is 2,44. Conclusion: There is a significant difference of SNR value, no significant differences in CNR value and value of MRI pedis sequence Proton Density Fat Saturated sagittal detail is clear enough to show tendon achiles, bone marrow, joint space and not clear to show ekstra-articular fluids. STIR nice to show tendon achiles and bone marrow and clear enough to show ekstra-articular fluids and joint space.